Profile of unnatural deaths in a teaching hospital of West Bengal, India - Mitra, Satabdi; Panja, Saumabrata (International Journal Of Community Medicine And Public Health, 2020)
Background: Enquiry into unnatural deaths with all its manners being, suicidal, accidental or homicidal depends on circumstantial evidences for acceptable judgment in court of law. Objectives were to study socio-demographic characteristics of the study and to find out influencing factors, if any, behind these sudden, suspicious, undesirable deaths. Methods: A record-based, descriptive study with cross-sectional design was conducted for first six months of 2017 in NRS medical college hospital among 1603 unnatural deaths undergone police inquest. Besides the records obtained from medical record section, findings were corroborated from mortuary. Data were analyzed in SPSS 22.0 and Epi Info 7.0. Results: Mean age of the deceased was 37.18±17.42 years. Regarding cause of injury, more than 1/3rd (36.6%) was attributed to poisoning, followed by burn injury (24.8%), road traffic accidents (22.8%), fall from height (6.9%) and others the rest. Majority (68.3%) died within twenty hours of reaching the health care facility. More than half of the deceased committed suicide followed by accident and suicide the least. Binary logistic regression revealed, unnatural deaths inflicted by selves or others, i.e. suicide or homicide respectively, had statistically significant (p<0.05) association to productive age, urban residence, burn and RTA, longer survival and conservative nature of management. Conclusions: As suicide was found to comprise lion share of unnatural deaths, development and implementation of addressing the issue at all the levels, starting from individual to community is the need of the hour.